Arsenic species in atmospheric particulate matter as tracer of the air quality of Doñana Natural Park (SW Spain). (January 2015) - González-Castanedo, Y.; Sanchez-Rodas, D.; Sánchez de la Campa, A.M.; Pandolfi, M.; Alastuey, A.; Cachorro, V.E.; Querol, X.; de la Rosa, J.D.
Highlights: Arsenic species have been analyzed in airborne particulate matter from a Natural Park. As species proportion can been considered the copper smelter geochemical fingerprint. The presence of As species in Natural Park is linked to the wind transport scenarios. Abstract: Sampling and chemical analyses, including major compounds and trace elements, of atmospheric particulate matter (PM10 and PM2.5) have been performed during 2006–2007 in a regional background monitoring station located within the Doñana Natural Park (SW of Spain). This region is strategic for air quality and climate change studies, representing a meeting place of the European and African continents, and the Atlantic Ocean and Mediterranean Sea. The present study based on meteorological parameters demonstrated long-range transport and impact of industrial plumes on the Doñana Natural. Inorganic arsenic species (arsenate and arsenite) have been analyzed in particulate matter (PM) to characterize the impact of near Cu-smelter plumes and demonstrated the long-range transport of industrial pollutants. As(V) is the main specie of As and varies between 95% and 98% of total As in PM10 and 96–97% in PM2.5. The As(V)/As(III) ratio measured in emission plumes of a Cu-smelter are similar to the ratio found in the Doñana Natural Park. The application of Positive Matrix Factorization (PMF) to atmospheric particulate matter estimated the contributions and chemical profiles of natural and anthropogenic sources impacting the Natural Park, demonstrating the industrial origin of the As and other toxic elements in the air.